In vivo performance of near-infrared light transillumination for dentine proximal caries detection in permanent teeth - Ayşe Dündar; Mehmet Ertuğrul Çiftçi; Özlem İşman; Ali Murat Aktan (Elsevier, 2020)
Objective: The purpose of this in vivo study was to confirm the detection of proximal caries using near-infrared light transillumination (NILTI) (DIAGNOcam) device, and to compare the diagnostic performance of the device with other caries detection methods, including visual examination using the International Caries Detection and Assessment System (ICDAS), bitewing radiography (BW), an LED-based device (Midwest Caries I.D.), and a laser fluorescence device (LFpen). Methods: A total of 974 proximal surface of permanent posterior teeth from 34 patients (19 females and 15 males between the ages of 22-55) were evaluated in the present study. After clinical examination of each proximal surface by an experienced examiner, they were coded according to the ICDAS criteria and subsequently with BW, the NILTI, LED, and LFpen. The proximal dentin caries of 106 were opened based on the combination of visual, NILTI and radiographic assessment and validated; and were treated with restorative materials. The data were analyzed with descriptive statistics and calculation of the sensitivity, specificity, and area under curve (AUC). Results: The highest sensitivity values were recorded from NILTI readings (99.1%), followed by BW scores (86.8%). The highest specificity values were recorded from ICDAS (100%). The best AUC values were found from the NILTI readings (0.97), followed by BW (0.93) and ICDAS (0.87). Conclusion: The NILTI device exhibited the best performance in terms of detecting proximal dentin caries.